Self-Interested Framed and Prosocially Framed Messaging Can Equally Promote COVID-19 Prevention Intention: A Replication and Extension of Jordan et al.’s Study (2020) in the Japanese Context - Miyajima, Takeru; Murakami, Fumio (Frontiers in Psychology, 2021)
How can we effectively promote the public’s prevention of coronavirus disease 2019 (COVID-19) infection? Jordan et al. (2020) found with United States samples that emphasizing either self-interest or collective-interest of prevention behaviors could promote the public’s prevention intention. Moreover, prosocially framed messaging was more effective in motivating prevention intention than self-interested messaging. A dual consideration of both cultural psychology and the literature on personalized matching suggests the findings of Jordan et al. (2020) are counterintuitive, because persuasion is most effective when the frame of the message delivered and the recipient of the message are culturally congruent. In order to better understand the potential influence of culture, the current research aimed to replicate and extend Jordan et al. (2020) findings in the Japanese context. Specifically, we examined the question (1) whether the relative effectiveness of the prosocial appeal is culturally universal and robust, (2) which types of ‘others’ especially promote prevention intention, and (3) which psychological mechanisms can explain the impact of messaging on prevention intention. In Study 1 (N = 1,583), we confirmed that self-interested framed, prosocially framed, and the combination of both types of messaging were equally effective in motivating prevention intention. In Study 2 (N = 1,686), we found that family-framed messaging also had a promoting effect similar to that from self-interested and prosocial appeals. However, the relative advantage of prosocial appeals was not observed. Further, a psychological propensity relevant to sensitivity to social rejection did not moderate the impact of messaging on prevention intention in both studies. These results suggest that since engaging in the infection control itself was regarded as critical by citizens after public awareness of COVID-19 prevention has been sufficiently heightened, for whom we should act might not have mattered. Further, concerns for social rejection might have had less impact on the prevention intentions under these circumstances. These results suggest that the relative advantage of a prosocial appeal might not be either culturally universal or prominent in a collectivistic culture. Instead, they suggest that the advantages of such an appeal depends on the more dynamic influence of COVID-19 infection.